Beyond the Label: Multidimensional Brand Equity Driving Apparel Visibility Through Customer Satisfaction - Obeto, Mercy Nwadiuto; Munap, Rudzi Binti (International Review of Management and Marketing, 2026)
Apparel brand companies need strong brand visibility and multidimensional brand equity to satisfy customers and remain relevant in a competitive market. The study examined the relationship between perceived quality, brand attitude, purchasing behaviour, on brand visibility, and the mediating role of customer satisfaction. A quantitative research design was employed with the use of simple random sampling; 363 questionnaires was disseminated online using google forms to apparel brands customers in Klang Valley using 5-point Likert scale. The measurement model confirms that the model fits the data. The structural equation model analysed the hypothesised relationship between the variables. The findings of the study indicated that there was a significant positive relationship between perceived quality, brand attitude, customer satisfaction, and brand visibility. However, there was no significant relationship between purchasing behaviour and brand visibility. Customer satisfaction does not mediate the relationship between perceived quality and brand visibility. Furthermore, customer satisfaction mediates the relationship between brand attitude, purchasing behaviour, and brand visibility. The study offers practical and theoretical contribution for apparel brand companies, guiding them in strengthening their brands' multidimensional equity across different market segments, improve visibility by focusing on customer satisfaction.